Новое свойство молекул нейтральной газовой среды - Делов, И. А.; Слипченко, Н. И.; Леонидов, А. А. (ХНУРЭ, 2008)
The results of theoretical and experimental investigations demonstrating existence of a new property of a neutral gaseous medium molecule, namely, the property to retain direction and velocity value received by them from the external sources are obtained. This property of the gaseous medium makes it possible to explain in what a way the molecular processes of anisotropy is observed in experiments.
Keywords: газовая среда; нейтральная газовая среда; анизотропия молекулярных процессов